1990
DOI: 10.1002/ar.1092270302
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glyoxylate cycle enzymes in chick liver—the effect of vitamin D3: Cytochemistry and biochemistry

Abstract: Information regarding the presence of the glyoxylate cycle in chick liver was sought. This metabolic pathway has long been thought to be absent from vertebrate tissues. Previous studies in other tissues have shown that, when present, this pathway is sensitive to vitamin-D. Thus, the effect of long-term vitamin-D deficiency and subsequent vitamin-D replacement on liver structure was studied by light microscopy. In addition, specific biochemical assays for the presence of glyoxylate cycle enzymes were performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…The difference in expression level is difficult to interpret and might be due to either stimulation at a higher single dose of propylene glycol, or downregulation by a repeated exposure to a lower dose, or vice versa; the total dose administered in both cases being nearly the same. With a single dose of propylene glycol no effect was found on peroxisomal -oxidation activity, or on malate synthase or isocitrate lyase activities in chick liver homogenates as compared with the control not receiving propylene glycol (Davis et al 1990). On cytosolic and microsomal enzyme activities also, some effects of propylene glycol were reported by Yamamoto & Adachi (1978).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The difference in expression level is difficult to interpret and might be due to either stimulation at a higher single dose of propylene glycol, or downregulation by a repeated exposure to a lower dose, or vice versa; the total dose administered in both cases being nearly the same. With a single dose of propylene glycol no effect was found on peroxisomal -oxidation activity, or on malate synthase or isocitrate lyase activities in chick liver homogenates as compared with the control not receiving propylene glycol (Davis et al 1990). On cytosolic and microsomal enzyme activities also, some effects of propylene glycol were reported by Yamamoto & Adachi (1978).…”
Section: Discussionmentioning
confidence: 85%
“…Further indication for a possible role of VD in the regulation of the peroxisomal compartment is provided by studies that demonstrated peroxisome proliferation in chicken liver (Davis et al 1990) and gut epithelium (Davis & Jones 1984) in response to VD. The same authors have demonstrated induction by VD of peroxisomal -oxidation in rat liver (Davis et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…4). In the present investigation the key enzymes of the glyoxylate cycle, isocitrate lyase and malate synthase, have been demonstrated in liver extracts of food-starved rats. To date, there has only been scarce evidence for the glyoxylate cycle in animals, except in larvae of lower invertebrates in which it serves for utilization of stored fats for gluconeogenesis during growth [14], in some detailed instances in vertebrates [4,5], and in cartilage tissue of the epiphyseal growth plate of rats [6]. The reason for the present finding was that we used starved rats and analyzed these enzymes in liver tissues.…”
Section: Fraction Numbermentioning
confidence: 92%
“…Glyoxylate cycle activities have also been discovered in some animal tissues such as larvae of nematodes, urinary bladder epithelium cell layer of Buffus marinus [4], and liver of chicken which, after suffering from vitamin D deficiency, was replenished with vitamin D [5]. In mammals, glyoxylate cycle activities have only been found in cartilage tissue of the epiphyseal growth plate of rats [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this metabolic pathway in animals is controversial. ICL and MS activities have been reported in birds and amphibians (Davis et al, 1986(Davis et al, , 1990) and a recent comparative genomic study showed the presence of an ICL gene in nematodes and cnidaria and an MS gene in nematodes, cnidaria, echinoderms, amphibians, fish, and insects. Interestingly, in placental mammals the MS gene is a pseudogene and the ICL gene is absent (Kondrashov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%